(3fXe GdeYdheGJ GdeMGSHjIs - (3ceGd GdOjf eUWai(B, (3GdOgQGhjs ((3GdEScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2002)
(3GdeaGgje GdGSGSjI dfXe GdeYdheGJ , JTZjd GdeYdheGJ aj fXGe GdeYdheGJ GdeMGSHj, OhQGJ GdYedjGJ(B- (3fXe GdeYdheGJ GdbGFeI Ydi GdMGSHGJ GdEdcJQhfjI GdeJbOeIs
Keywords: (3GdeMGSHIs; (3fXe GdeYdheGJs